2011
DOI: 10.1021/ja206745w
|View full text |Cite
|
Sign up to set email alerts
|

Iron–Copper Cooperative Catalysis in the Reactions of Alkyl Grignard Reagents: Exchange Reaction with Alkenes and Carbometalation of Alkynes

Abstract: Iron-copper cooperative catalysis is shown to be effective for an alkene-Grignard exchange reaction and alkylmagnesiation of alkynes. The Grignard exchange between terminal alkenes (RCH═CH(2)) and cyclopentylmagnesium bromide was catalyzed by FeCl(3) (2.5 mol %) and CuBr (5 mol %) in combination with PBu(3) (10 mol %) to give RCH(2)CH(2)MgBr in high yields. 1-Alkyl Grignard reagents add to alkynes in the presence of a catalyst system consisting of Fe(acac)(3), CuBr, PBu(3), and N,N,N',N'-tetramethylethylenedia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
80
2
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(85 citation statements)
references
References 36 publications
1
80
2
2
Order By: Relevance
“…[154] It was suggested that the alkene by-product produced during the reaction might act as a stabilising ligand on iron. In contrast to previous reports by Shirakawa and Hayashi [147] and Ready [155] on the iron-catalysed addition of alkyl Grignard reagents to di-substituted alkynes and (homo)propargylic alcohols, respectively, no products arising from carbomagnesiation were reported by Nakamura. It was unclear why 2 equivalents of ethylmagnesium bromide were required, as unreacted ethylmagnesium bromide remained at the end of reaction; however, lower equivalents of ethylmagnesium bromide led to inferior yields of hydromagnesiation products.…”
Section: Hydromagnesiationcontrasting
confidence: 90%
See 1 more Smart Citation
“…[154] It was suggested that the alkene by-product produced during the reaction might act as a stabilising ligand on iron. In contrast to previous reports by Shirakawa and Hayashi [147] and Ready [155] on the iron-catalysed addition of alkyl Grignard reagents to di-substituted alkynes and (homo)propargylic alcohols, respectively, no products arising from carbomagnesiation were reported by Nakamura. It was unclear why 2 equivalents of ethylmagnesium bromide were required, as unreacted ethylmagnesium bromide remained at the end of reaction; however, lower equivalents of ethylmagnesium bromide led to inferior yields of hydromagnesiation products.…”
Section: Hydromagnesiationcontrasting
confidence: 90%
“…[147] A combination of FeCl 3 (2.5 mol %), CuBr (5 mol %) and tributylphosphine (10 mol %) was found to be effective for the hydromagnesiation of terminal aliphatic alkenes by using cyclopentylmagnesium bromide (281) as the stoichiometric hydride source (Scheme 62 A). As internal alkenes were found to be unreactive under the reaction conditions, the formation of cyclopentene (282) following "HÀMgX" transfer from cyclopentylmagnesium bromide (281) effectively removed this alkene by-product from the reaction and led to the formation of hydrofunctionalised products 283 in generally high yields.…”
Section: Hydromagnesiationmentioning
confidence: 99%
“…Several alkene hydrocarboxylations have been reported, including some that provide chiral molecules, however, all but one yield racemic mixtures. 12,13,14,16,49,103 A particular challenge is the need for additives that promote catalyst regeneration and product release. 12,13,14,49 These additives may interfere with the ability to make reactions enantioselective: for example, known iron-based hydrocarboxylation catalysts depend on Grignard reagents, 13 109,111,112 The regioselectivity may differ from the example shown here.…”
Section: Asymmetric Hydrocarboxylation Vs Asymmetric Hydrogenationmentioning
confidence: 99%
“…The involvement of nickel hydride species was slightly more favorable energetically, with a significantly lower energetic difference for electron-rich substrates, an observation that could explain their lack of reactivity. As for the nickel hydride Prompted by the seminal work of Rovis on the Ni-carboxylation of styrenes [76] as well as by the work of Hayashi and Shirakawa on the Fe-and Cu-catalyzed hydromagnesiation of terminal alkenes [78], Thomas reported the preparation of α-methyl arylacetic acids in the presence of cheap and bench-stable iron/bis(imino)pyridine catalyst and Grignard reagents at room temperature (Scheme 21).…”
Section: Catalytic Reductive Carboxylation Of Alkenes With Comentioning
confidence: 99%